Hardness uniformity survey of butt joint from friction stir processing for magnesium-based aluminium alloy plate - Jantarasricha, Tanakorn; Suwichien, Narisara; Kunhirunbawon, Siridech (Engineering and Applied Science Research, 2023)
In metal welding circles, it is commonly acknowledged that the ideal weld is one that appears to have no connections. The properties of the weld seam must not generate defects or unevenness that vary considerably from the original metal. The objective of this research was to explore into the hardness uniformity of the friction stir weld of AA5083-H112 aluminium composite plate, using factorial experimental design theory to determine the welding process. The experiment was carried out with the rotational speed and feed-rate of each variable adjusted at three levels. Afterwards, the statistical results of the hardness measured from the stirring friction weld were examined. At a 95% confidence level, an analysis revealed that a rotational speed of 4,500 rpm and a feed-rate of 72.91 mm/min resulted in a weld hardness equivalent to the original metal hardness. However, there are constraints on machinery and equipment. Therefore, the rotational speed of 4,500 rpm and feed rate of 55 mm/min were the testing parameters that produced the predicted hardness value of 38.49 HRB. Finally, the previously described weld zone remains subject to 197 MPa of residual compressive stress.